Penerapan Model Pembelajaran Project Based Learning (PBL) untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS di Kelas IX Mts Darul Ulum, Ngembalrejo, Bae, Kudus - Alfiyah Alfiyah; Laily Fu’adah (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the implementation of the Project Based Learning (PBL) model to enhance student achievement in Social Studies (IPS) for Grade IX at MTs Darul Ulum Nembalrejo, Kudus. The background of the research highlights that many students experience difficulties understanding the material due to a lack of motivation and concentration, influenced by the demanding schedules at the boarding school. By applying PBL, students are encouraged to actively design and solve problems through a series of learning activities that emphasize experimentation, discussion, and collaboration. This model is expected not only to improve conceptual understanding but also to enhance students’ social and creative skills, while producing high-quality learning outcomes. Furthermore, the study contributes to the development of more effective teaching methods in educational settings by providing opportunities for integrating theoretical knowledge with practical experiences in everyday life. The obtained results are anticipated to stimulate an overall improvement in Social Studies learning quality and reinforce the teacher’s role as an active facilitator in the teaching and learning process.